(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objective: To identify the risks for the development of friction injury (FI) in long-lived elderly in primary health care. Methods: Descriptive research of quantitative approach. Participants were 42 elderly aged 80 years or more. Conducted structured interview and applied form. Simple descriptive analysis was realized by means of the absolute and relative frequency of the variables. Verified the level of signifi cance between the most frequent clinical factors and sociodemographic factors: age, ethnicity and gender, using the chi-square test or Fisher’s exact test. The contingency coeffi cient was performed with the parameters: c ≥ 0.750 = strong association; 0.500 to 0.749 = moderate association; ≤ 0.499 = weak association. Results: Age ranged from 80 to 100 years, prevailing between 80 and 85 years (59.5%), 28 (66.7%) women, 38 (90.5%) white and 30 (71.4%) with incomplete first degree. In 41 elderly patients (97.6%), there were dermatological alterations related to the risk for FI (dry skin, senile blemish, ecchymosis and edema). Age was the demographic factor with the highest association with clinical fi ndings (p = 0.0397). Conclusion: Faced with these fi ndings, it becomes imperative that nurses be equipped with scientifi c knowledge, which allow them to propose care capable of controlling the risk factors for FI development.